2006
DOI: 10.1002/tox.20215
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heavy metals and PCBs on marine picoplankton

Abstract: Synergistic/antagonistic effects of multiple contaminants in marine environments are almost completely unexplored. In the present study, we investigated the effects of heavy metals (Zn and Pb) and PCBs on picoplankton abundance, biomass, cell size distribution, and bacterial C production. Natural picoplankton assemblages were exposed to heavy metals (Zn or Pb), organic contaminants (PCBs, Aroclor 1260), and to a mixture of different contaminants. The results of the present study indicate that Zn addition stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 71 publications
(65 reference statements)
1
18
0
Order By: Relevance
“…In the present study, the interactions for reduced GSH content were mostly synergistic but additive or antagonistic for SOD activity. A possible antagonistic effect on the abundance, biomass, and bacterial carbon production of picophytoplankton was also found between the polychlorinated biphenyl compound Aroclor 1260 coupled with the addition of heavy metals (Zn and Pb) [16]. Both antagonistic and additive interactions on the growth Fig.…”
Section: Toxicity Of Cocontamination To Free Microalgae and Interactimentioning
confidence: 82%
See 1 more Smart Citation
“…In the present study, the interactions for reduced GSH content were mostly synergistic but additive or antagonistic for SOD activity. A possible antagonistic effect on the abundance, biomass, and bacterial carbon production of picophytoplankton was also found between the polychlorinated biphenyl compound Aroclor 1260 coupled with the addition of heavy metals (Zn and Pb) [16]. Both antagonistic and additive interactions on the growth Fig.…”
Section: Toxicity Of Cocontamination To Free Microalgae and Interactimentioning
confidence: 82%
“…However, most of these studies were mainly on the toxicity of single contaminants; research on the combined toxic effects of more than one group of contaminants in microalgae is limited [13,14]. Limited research suggested that the effects of cocontamination on the growth of autotrophic and heterotrophic microorganisms differed greatly from the effect of single contaminants [15,16]. It is essential to evaluate the combined toxicity of pollutants on microalgae, which are not only ubiquitous but also the primary producers in aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Already studies have demonstrated that metals can exert a toxic effect to marine phyto-and zooplankton species (e.g., Hirota, 1981;Hu, 1981;Moraitouapostolopoulou and Verriopoulos, 1982;Caroppo et al, 2006;Fuchida et al, 2017) and can lead to metal accumulation (bioaccumulation) in higher trophic levels of food chains (Amiard Triquet et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the effect of Zn on bacteria have been carried out in freshwater environments (Nweke et al 2006, Vega-López et al 2007; the results have shown a strong suppression of bacterial growth at low concentrations (> 0.1 μg Zn l -1 ), which is about an order of magnitude lower than the effective level on phytoplankton (Paulsson et al 2000). Although there have been just a few studies on the effects of Zn on marine bacterial communities (Ku$pilić et al 1989, Caroppo et al 2006, RochelleNewall et al 2008, these studies, too, have suggested that the activity of marine bacteria is also inhibited by the addition of Zn at 1 to 100 μg Zn l -1 . However, the impact on marine bacteria might be a little weak when compared with that on phytoplankton (Caroppo et al 2006, Rochelle-Newall et al 2008, and it was suggested that Zn induces a shift to a bacteria-dominated heterotrophic system.…”
mentioning
confidence: 99%
“…Although there have been just a few studies on the effects of Zn on marine bacterial communities (Ku$pilić et al 1989, Caroppo et al 2006, RochelleNewall et al 2008, these studies, too, have suggested that the activity of marine bacteria is also inhibited by the addition of Zn at 1 to 100 μg Zn l -1 . However, the impact on marine bacteria might be a little weak when compared with that on phytoplankton (Caroppo et al 2006, Rochelle-Newall et al 2008, and it was suggested that Zn induces a shift to a bacteria-dominated heterotrophic system. Considering that bacterial activity is closely related to DOM remineralisation (Kirchman et al 1991, Zn input into coastal zones will result in an alteration of DOM dynamics.…”
mentioning
confidence: 99%